ISLAMIC EDUCATION AND CHARACTER DEVELOPMENT: CHARACTER CRISIS ANALYSIS - Imam Tabroni; Lani Rahmawati (Education : Jurnal Sosial Humaniora dan Pendidikan, 2021)
Islamic Religious Education is a subject that is considered effective in shaping the character of students. Character education will grow well if it starts from the embedded religious spirit in children, therefore PAI material in schools is one of the supports for character education. Through PAI learning students are taught aqidah as their religious basis, taught the Koran and hadith as a guide for their lives, taught fiqh as legal signs in worship, teaches Islamic history as an example of life, and teaches morals as a guide for human behavior whether in the good or bad category. bad . Therefore, the main goal of PAI learning is the formation of personality in students which is reflected in their behavior and mindset in everyday life.